Activation of OR1A1 suppresses PPAR-γ expression by inducing HES-1 in cultured hepatocytes. (July 2015) - Wu, Chunyan; Jia, Yaoyao; Lee, Ji Hae; Kim, Yeonji; Sekharan, Sivakumar; Batista, Victor S.; Lee, Sung-Joon
Graphical abstract: Highlights: OR1A1 is significantly expressed on the cell surface of HepG2 cultured hepatocytes. OR1A1 activation by (−)-carvone activates PKA-CREB-HES-1 signaling axis. OR1A1 activation reduces intracellular triglyceride concentrations in HepG2 cells. Abstract: Olfactory receptors (ORs) comprise the largest G protein-coupled receptor gene superfamily. Recent studies indicate that ORs are also expressed in non-olfactory organs, including metabolically active tissues, although their biological functions in these tissues are largely unknown. In this study, OR1A1 expression was detected in HepG2 liver cells. OR1A1 activation by (−)-carvone, a known OR1A1 ligand, increased the cyclic adenosine monophosphate (cAMP), but not intracellular Ca 2+ concentration, thereby inducing protein kinase A (PKA) activity with subsequent phosphorylation of cAMP response element-binding protein (CREB) and upregulation of the CREB-responsive gene hairy and enhancer of split (HES)-1, a corepressor of peroxisome proliferator-activated receptor-γ (PPAR-γ) in hepatocytes. In (−)-carvone-stimulated cells, the repression of PPAR-γ reduced the expression of the target gene, mitochondrial glycerol-3-phosphate acyltransferase, which encodes a key enzyme involved in triglyceride synthesis. Intracellular triglyceride level and lipid accumulation were reduced in cells stimulated with (−)-carvone, effects that were diminished following the loss of OR1A1 function. These results indicate that OR1A1 may function as a non-redundant receptor in hepatocytes that regulates the PKA-CREB-HES-1 signaling axis and thereby modulates hepatic triglyceride metabolism.